On the prime graph question for integral group rings of Conway simple groups. (November 2019) - Margolis, Leo
Abstract: The Prime Graph Question for integral group rings asks if it is true that if the normalized unit group of the integral group ring of a finite group G contains an element of order pq, for some primes p and q, also G contains an element of that order. We answer this question for the three Conway sporadic simple groups after reducing it to a combinatorial question about Young tableaux and Littlewood-Richardson coefficients. This finishes work of V. Bovdi, A. Konovalov and S. Linton.